STRATEGI PENGEMBANGAN MADRASAH DINIYAH SEBAGAI ALTERNATIF PENDIDIKAN KEISLAMAN UNGGULAN - Triana Rosalina Noor; Rodiah, Siti (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2024)
This qualitative research aims to provide an overview of the strategy for developing Diniyah Madrasah as an alternative to superior Islamic education at Madrasah Diniyah Raudlatul Ulum Manggisan Lumajang. Data collection methods used interview data, observation and documentation. The selection of research subjects was carried out purposively with two people, namely the head of the madrasah and the teacher, taking into account that they had in-depth information regarding the research object. The results of this research were analyzed descriptively referring to four predetermined strategy categories, namely integration, intensive, diversification and defensive strategies. The research results show that the integration strategy involves collaboration with external parties, expanding networks, and integrating the madrasah curriculum with the government curriculum, which provides positive results. Intensive strategies focus on developing teaching and learning programs, while diversification strategies include updating learning models and methods. Defensive strategies seek to maintain learning traditions and culture. The main supporting factors are competent teachers, support from student guardians and the community, and adequate facilities. However, the challenges include limited teachers, limited learning space, lack of motivation for some teachers to improve their knowledge, and school administration which is still in the stage of improvement.